The Development of Student Worksheets (LKPD) Enviromental Change as Learning Resource for Class X Student of SMA Negeri 2 Wonosobo to Grow Attitude of Enviromental Cleanliness - Adina, Winardita Putri; Ngabekti, Sri (FMIPA UNNES, 2022)
This study aims to determine the level of validity of Student Worksheet environmental change as learning resources for class X student of SMA Negeri 2 Wonosobo to grow attitude of environmental cleanliness. This type of research is research and development (Research of Development). The research and development model used is a procedural model. The types of instruments needed to measure the effectiveness of the teaching materials developed is questionnaires. The data analysis in this study is the analysis of validity. Analysis of non-test instrument data in this study used descriptive data analysis techniques using a Likert Scale. The results showed that the research and development that had been carried out resulted in a learning medium, namely the Student Worksheet (LKPD) environmental change as learning resources for class X student of SMA Negeri 2 Wonosobo to grow attitude of environmental cleanliness. From these results, it can be concluded that the implementation of LKPD shows results that meet the feasibility. The need for LKPD development on waste management as a learning resource for students who are able to foster an attitude of environmental conservation on environmental change materials, including appearance, consistency, use of letters, physical criteria, material/quality of content, presentation and language. These needs are important to be developed so that students are more active and can stimulate students to think critically about the material being studied by class X students of SMA Negeri 2 Wonosobo.